2020
DOI: 10.1039/d0cc05335j
|View full text |Cite
|
Sign up to set email alerts
|

A two-photon fluorescence self-reporting black phosphorus nanoprobe for the in situ monitoring of therapy response

Abstract: The in situ and real-time supervising of reactive oxygen species (ROS) generated during the photodynamic therapy (PDT) is of great significance for lessening the nonspecific damage and guiding personalized therapy....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Guan et al reported a black phosphorus-based two-photon nanoprobe (TPBP), the 1 O 2 generated by TPBP activated the two-photon molecule to emit a fluorescence signal under laser irradiation, and the tumor growth inhibition rate was positively correlated with the fluorescence signal ( R 2 = 0.989). 188…”
Section: Cancer Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Guan et al reported a black phosphorus-based two-photon nanoprobe (TPBP), the 1 O 2 generated by TPBP activated the two-photon molecule to emit a fluorescence signal under laser irradiation, and the tumor growth inhibition rate was positively correlated with the fluorescence signal ( R 2 = 0.989). 188…”
Section: Cancer Stratificationmentioning
confidence: 99%
“…Guan et al reported a black phosphorus-based two-photon nanoprobe (TPBP), the 1 O 2 generated by TPBP activated the two-photon molecule to emit a fluorescence signal under laser irradiation, and the tumor growth inhibition rate was positively correlated with the fluorescence signal (R 2 = 0.989). 188 Wang et al reported a photosensitizer called NG-cRGD, which consisted of a cyclic pentapeptide (cRGD) that specifically targeted integrin avb3 in tumors, and a 2-cyano-4nitrobenzene-1-sulfonyl group that was responsive to glutathione. 189 NG-cRGD incorporated a strong electronabsorbing group that effectively inhibited the breaking of CQC bonds and the associated phototoxicity.…”
Section: Pdtmentioning
confidence: 99%
“…The 1 O 2 generation was measured using DPBF as a capture agent after treatment with light irradiation of PLU@PTc hydrogels (PLU@PTc/light) and PTc NPs (PTc/light) using PLU@PTc and PTc treatments as controls. 26 Briefly, hydrogel disks (ϕ 8 mm × 2 mm) were first incubated in pH 5.5 buffers for 4 h, and then 10 mL of DPBF solution in dimethyl sulfoxide (20 μg/mL) was added in the dark for 1 h. The mixture was exposed to a 660 nm laser for different time periods, and the UV−Vis absorption spectra were recorded.…”
Section: 7mentioning
confidence: 99%
“…A growing number of studies have demonstrated that highly activated photosensitizers can destroy normal cells, compromising therapeutic efficacy . Moreover, the post-PDT safety problem means the disposition of the photosensitizers by body after therapy, which has attracted increasing attention in recent years. Obviously, real-time monitoring of photosensitizers in the body and evaluating the exact treatment end point are especially important for PDT under dosimetric guidance. Unfortunately, additional fluorescent probes need to be introduced into most current PDTs, which makes the monitoring process complicated and delayed.…”
Section: Introductionmentioning
confidence: 99%